2009
DOI: 10.1038/onc.2009.139
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage-independent cell growth signature identifies tumors with metastatic potential

Abstract: The oncogenic phenotype is complex, resulting from the accumulation of multiple somatic mutations that lead to the deregulation of growth regulatory and cell fate controlling activities and pathways. The ability to dissect this complexity, so as to reveal discrete aspects of the biology underlying the oncogenic phenotype, is critical to understanding the various mechanisms of disease as well as to reveal opportunities for novel therapeutic strategies. Previous work has characterized the process of anchorageind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
268
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(283 citation statements)
references
References 39 publications
12
268
1
2
Order By: Relevance
“…These experiments revealed that the knockdown of FUT9 in both cell lines significantly increases their expansion compared to matching non‐targeting sh RNA controls (Fig 3A). In agreement, FUT9 silencing also enhanced anchorage‐independent growth in soft agar (Mori et al , 2009) (Fig 3B). Moreover, the loss of FUT9 augmented the ability of cancer cells to form colonies in monolayers, when cells were seeded at very low densities (Fig 3D).…”
Section: Resultssupporting
confidence: 85%
“…These experiments revealed that the knockdown of FUT9 in both cell lines significantly increases their expansion compared to matching non‐targeting sh RNA controls (Fig 3A). In agreement, FUT9 silencing also enhanced anchorage‐independent growth in soft agar (Mori et al , 2009) (Fig 3B). Moreover, the loss of FUT9 augmented the ability of cancer cells to form colonies in monolayers, when cells were seeded at very low densities (Fig 3D).…”
Section: Resultssupporting
confidence: 85%
“…In vitro anchorage-independent colony growth embedded in soft agar is an important assessment of tumorigenicity [21], and is considered to be predictive of the ability of tumor cells to form new metastases in vivo [25], so inhibition of this growth by KR-33028, even in the non-tumorigenic Hs578T cells, is noteworthy. However, despite the efficacy of KR-33028 in limiting colony growth in TNBC cells, the drug did not affect cell proliferation at non-cytotoxic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Anchorage-independent growth is therefore a major characteristic of transformed cells, and in fact shows a good correlation with tumor malignancy. 38,39 In addition to cancer cells, Zfp57 is involved in ES cell anchorage-independent growth, suggesting that ZFP57-mediated anchorage-independent growth is not restricted to cancer cells. Furthermore, ZFP57…”
Section: Discussionmentioning
confidence: 99%